THE PLACE OF CRYPTOCURRENCY AND BITCOIN IN THE ERA OF THE DIGITAL ECONOMY (E Global Congress, 2025)
This article presents information about cryptocurrency centralization, volatility and investments, cryptocurrency transfer, cryptocurrency purchase, negative and positive aspects,Bitcoin and its structure.